More than one in three proxies do not know their loved one’s current code status: An observational study in a Maryland ICU - Turnbull, Alison E.; Chessare, Caroline M.; Coffin, Rachel K.; Needham, Dale M. (PloS one, 2019)
The majority of ICU patients lack decision-making capacity at some point during their ICU stay. However the extent to which proxy decision-makers are engaged in decisions about their patient's care is challenging to quantify. To assess 1)whether proxies know their patient's actual code status as recorded in the electronic medical record (EMR), and 2)whether code status orders reflect ICU patient preferences as reported by proxy decision-makers. We enrolled proxy decision-makers for 96 days starting January 4, 2016. Proxies were asked about the patient's goals of care, preferred code status, and actual code status. Responses were compared to code status orders in the EMR at the time of interview. Characteristics of patients and proxies who correctly vs incorrectly identified actual code status were compared, as were characteristics of proxies who reported a preferred code status that did vs did not match actual code status. Among 111 proxies, 42 (38%) were incorrect or unsure about the patient's actual code status and those who were correct vs. incorrect or unsure were similar in age, race, and years of education (P>0.20 for all comparisons). Twenty-nine percent reported a preferred code status that did not match the patient's code status in the EMR. Matching preferred and actual code status was not associated with a patient's age, gender, income, admission diagnosis, or subsequent in-hospital mortality or with proxy age, gender, race, education level, or relation to the patient (P>0.20 for all comparisons). More than 1 in 3 proxies is incorrect or unsure about their patient's actual code status and more than 1 in 4 proxies reported that a preferred code status that did not match orders in the EMR. Proxy age, race, gender and education level were not associated with correctly identifying code status or code status concordance.